The AGT M235T (RS699, 4072T>C) polymorphism is not associated with elite weightlifting performance - Ben-Zaken, S.; Meckel, Y.; Nemet, D.; Pantanowitz, M.; Eliakim, A. (Acta Kinesiologiae Universitatis Tartuensis, 2018)
It is now well established that genetic background influences an athlete`s ability to excel in different sport disciplines. Previous studies have demonstrated that among power athletes, single nucleotide polymorphism (SNP) in the AGT genotype (Thr-Thr), was significantly more prevalent among weightlifters compared to sprinters and jumpers indicating that despite the common features of these sport subtypes (short and very intense), they vary in their strength and speed abilities, as well as in their genetic make-up. The aim of the present study was to assess whether the AGT SNP can be used also to distinguish elite from national levels weightlifters. The AGT M235T genotype frequencies were assessed in 47 weightlifters (30 elite, 17 national level) and 86 non-athletes control. The Thr-Thr genotype was significantly higher among weightlifters (29.8%) compared to controls (12.8%) (p=0.048). Thr allele frequency was significantly higher among weightlifters (55.3%) compared to controls (37.8%) (p=0.021). However, there was no difference in the prevalence of the polymorphism between national level and elite athletes. In conclusion, the results suggest that the AGT polymorphism cannot predict elite competitive weightlifting performance.